SINTESIS DAN KARAKTERISASI POLI(ETILEN GLIKOL-B-STEARIL-CO-METIL GLUTAMAT) - (NIM 20506021), LENGGANA
Polyglutamates are a class of polypeptides, usually with a stable a-helix secondary structure. This helix structure gives possibility to create a large combined dipole moment by aligning the orientation of the helices. Materials based on these helices can be useful in micro-electronical and electro-optical applications. The aim of this study is to synthesize and characterize new copolymers of poly(ethylene glycol-b-stearyl-co-methyl glutamate) (PEG-b-SMLG) and also to construct a double brush monolayer at water-air interface. Various compositions of PEG-b-SMLG were prepared by ring-opening polymerization of y-methyl-L-glutamate-N-carboxy anhydride (MLG-NCA) and y-stearyl-L-glutamate-N-carboxy anhydride (SLG-NCA) with a-methxoxy-w-amino-polyethylene glycol (PEG-NH2) as an initiator. The block ratio and chain length were varied while the composition of polyglutamate was maintained 30% (mol/mol) SLG and 70% (mol/mol) MLG. The purity of the products was confirmed by GPC, MALDI-TOF and 1H-NMR analysis. FTIR spectra proved that all copolymers have a-helix conformation. Langmuir-Blodgett (LB) isotherm of the copolymers shows the presence of three phase transitions. The phases at surface area below ~15 A2/unit indicate the helices orientation changes. It also observed that this phase disappears as n-hexadecane was added to the monolayer.